Pengaruh Pengendalian Internal Dan Whistleblowing System Terhadap Pencegahan Kecurangan Akuntansi Pada Lembaga Perkreditan Desa Se-Kecamatan Abiansemal - Mulyawati, Dewa Ayu Made; Kusumawati, Ni Putu Ayu; Ayu, Putu Cita (UNHI Press, 2025)
Fraud is unlawful action involving deceit, concealment, or violation of trust and often serves as a precursor to more serious criminal acts like corruption. The effectiveness of internal controls and the existence of a whistleblowing system are key factors influencing accounting fraud. This study aims to know the impact of these factors on preventing accounting fraud in Village Credit Institutions. The study surveyed 147 members of the Supervisory Board for Village Credit Institutions in Abiansemal District. Data analysis methods included multiple linear regression, coefficient of determination, t-test, and f-test. The findings indicate that both the effectiveness of internal controls and the whistleblowing system have a significant positive influence on preventing accounting fraud. Recommendations for the Village Credit Institutions in Abiansemal District include maintaining and enhancing measures to prevent or minimize accounting fraud to achieve organizational objectives. Strengthening internal controls and whistleblowing systems are essential steps in preventing accounting fraud.